Post-Bellum, Pre-Harlem : African American Literature and Culture, 1877-1919. - McCaskill, Barbara (NYU Press, 2006)
The years between the collapse of Reconstruction and the end of World War I mark a pivotal moment in African American cultural production. Christened the "Post-Bellum-Pre-Harlem" era by the novelist Charles Chesnutt, these years look back to the antislavery movement and forward to the artistic flowering and racial self-consciousness of the Harlem Renaissance. Post-Bellum, Pre-Harlem offers fresh perspectives on the literary and cultural achievements of African American men and women during this critically neglected, though vitally important, period of our nation's past. Using a wide range of d.